2015
DOI: 10.1016/j.juro.2014.11.056
|View full text |Cite|
|
Sign up to set email alerts
|

The Natural History of Nonobstructing Asymptomatic Renal Stones Managed with Active Surveillance

Abstract: Among asymptomatic nonobstructing renal calculi managed with active surveillance, most remained asymptomatic through an average followup of more than 3 years. Less than 30% caused renal colic, less than 20% were operated on for pain and 7% spontaneously passed. Lower poles stones were significantly less likely to cause symptoms or pass spontaneously. Despite 3 stones causing silent hydronephrosis suggestive of obstruction, regular followup imaging facilitated interventions that prevented renal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 11 publications
1
51
0
4
Order By: Relevance
“…Optimal management of low‐risk patients is debatable and evidence on the management of asymptomatic calyceal stones is heterogeneous, making definitive recommendations difficult. Studies that have evaluated the natural history of asymptomatic calyceal stones have reported conflicting results with stone progression rates ranging from 32% to 77%, and spontaneous stone‐passage rates between 12.5% and 29.1% .…”
Section: Introductionmentioning
confidence: 99%
“…Optimal management of low‐risk patients is debatable and evidence on the management of asymptomatic calyceal stones is heterogeneous, making definitive recommendations difficult. Studies that have evaluated the natural history of asymptomatic calyceal stones have reported conflicting results with stone progression rates ranging from 32% to 77%, and spontaneous stone‐passage rates between 12.5% and 29.1% .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 160 stones, Dropkin et al found that upper or mid pole stones were more likely to become symptomatic and require intervention. 4 They also found that a small number developed silent obstruction, providing a good argument for follow-up imaging.…”
Section: Surveillancementioning
confidence: 95%
“…65%). There were 41 stone episodes with 98 individual stones identified with a mean stone size of 4.9 mm (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Of the 41 episodes, 10 (24%) underwent surgery after initial diagnosis.…”
mentioning
confidence: 99%